MERANCANG FRAMEWORK POLICY INTERNET SEHAT PERGURUAN TINGGI - Barka Satya (Telematika, 2012)
Understanding the concept of a healthy internet policy framework in the context of this study is to analyze all forms of the level of interest in the use of internet in the college environment is properly used, as an analysis in determining or How to compile, Implementing, And Effectively And Efficiently manage, order objective Optimization Performance can be achieved